TEACHING LEARNING PROCESS OF VOCABULARY AT ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA - KARTIKAWATI, LINA (2011)
The research aims to describe the teaching learning process of vocabulary at English department of Muhammadiyah University of Surakarta. It is conducted to describe the methods implemented by the teacher and the strength and weakness of the teaching learning process of vocabulary at English department of Muhammadiyah University of Surakarta. The writer gets the data of this research from event, informants, and document. There are three techniques in collecting data namely: observation, interview, and document. The data are achieved from information related to the process teaching learning vocabulary, interview scripts, and document. The result of the analysis shows that the method used by the teacher is eclectic method, because the teacher chooses different methods to suite for his teaching purposes and situations. Those methods are Grammar Translation Method (GTM) and Cognitive Code Learning (CCL). This research has the strength and weakness. The strengths are the students get a lot of new vocabulary, the students are motivated to be active in the class, and the students are ready to know about the material that will be taught by the teacher. The weaknesses are the students often chat with their friends in the class, and the teacher does not use the other media of teaching-learning process.